Contagion in financial networks: a network theory and agent-based approaches to modeling the spread of risk in financial systems - Pinheiro, Leonardo dos Santos (2016)
This dissertation studies the spread of crisis over the financial system. More specifically, we aim to develop models that allow us to simulate how an economic shock strikes a few financial agents and from them propagate over the system, becoming a systemic problem. The dissertation is composed by the introduction and by two chapters. In the first chapter, we model the spread of crisis over investment funds using network science. Combining two models of propagation in financial networks, one simulating the propagation of losses in bipartite networks of assets and financial agents and the other simulating the propagation of losses in a network of cross-holdings of shares among financial agents, we develop an algorithm to simulate the spread of losses utilizing both mechanisms and we use this algorithm to simulate a crisis in the Brazilian market of investment funds. In Chapter 2 we develop an agent-based simulation model, using financial agents to simulate the propagation of a shock affecting the repo market. We also create an artificial market consisting of banks, hedge funds and money market funds, and simulate the spread of a liquidity shock striking a risky securitized asset used as collateral in repurchase agreements.